Homer1a signaling in the amygdala counteracts pain-related synaptic plasticity, mGluR1 function and pain behaviors - Tappe-Theodor, Anke; Fu, Yu; Kuner, Rohini; Neugebauer, Volker (Molecular pain, 2011)
Background:Group I metabotropic glutamate receptor (mGluR1/5) signaling is an important mechanism of pain-related plasticity in the amygdala that plays a key role in the emotional-affective dimension of pain. Homer1a, the short form of the Homer1 family of scaffolding proteins, disrupts the mGluR-signaling complex and negatively regulates nociceptive plasticity at spinal synapses. Using transgenic mice overexpressing Homer1a in the forebrain (H1a-mice), we analyzed synaptic plasticity, pain behavior and mGluR1 function in the basolateral amygdala (BLA) in a model of arthritis pain.Findings:In contrast to wild-type mice, H1a-mice mice did not develop increased pain behaviors (spinal reflexes and audible and ultrasonic vocalizations) after induction of arthritis in the knee joint. Whole-cell patch-clamp recordings in brain slices showed that excitatory synaptic transmission from the BLA to the central nucleus (CeA) did not change in arthritic H1a-mice but increased in arthritic wild-type mice. A selective mGluR1 antagonist (CPCCOEt) had no effect on enhanced synaptic transmission in slices from H1a-BLA mice with arthritis but inhibited transmission in wild-type mice with arthritis as in our previous studies in rats.Conclusions:The results show that Homer1a expressed in forebrain neurons, prevents the development of pain hypersensitivity in arthritis and disrupts pain-related plasticity at synapses in amygdaloid nuclei. Furthermore, Homer1a eliminates the effect of an mGluR1 antagonist, which is consistent with the well-documented disruption of mGluR1 signaling by Homer1a. These findings emphasize the important role of mGluR1 in pain-related amygdala plasticity and provide evidence for the involvement of Homer1 proteins in the forebrain in the modulation of pain hypersensitivity.